2019
DOI: 10.1002/cam4.2426
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor 7 targets the vascular endothelial growth factor via the AKT/ERK pathway to regulate angiogenesis in colon cancer

Abstract: Background Studies have shown that CXCR7 is expressed in many tumors. The aim of the present study was to investigate the function of CXCR7 in colon cancer. Although evidence indicates that CXCR7 promotes angiogenesis in colon cancer, the mechanism involved in this process remains unclear. Methods The expression of CXCR7 in colon cancer was evaluated by quantitative reverse‐transcription polymerase chain reaction and western blotting. After transfection, cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…These results indicate that CXCR7 simultaneously regulates the ERK/AKT signaling pathway and expression of VEGF in colon cancer in vitro and in vivo. Our previous study revealed that CXCR7 is a key factor in tumorigenesis by promoting cell proliferation and angiogenesis (24). The results of the present study support the current conclusions and also indicate that changes in the expression of CXCR7 are key factors in the development and progression of colon cancer.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results indicate that CXCR7 simultaneously regulates the ERK/AKT signaling pathway and expression of VEGF in colon cancer in vitro and in vivo. Our previous study revealed that CXCR7 is a key factor in tumorigenesis by promoting cell proliferation and angiogenesis (24). The results of the present study support the current conclusions and also indicate that changes in the expression of CXCR7 are key factors in the development and progression of colon cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Over the last 8 years, a number of studies have confirmed that CXCR7 is also expressed in other types of cancer, such as pancreatic cancer, thyroid cancer, prostate cancer, breast cancer, esophageal cancer, liver cancer, and bladder cancer, and it has been shown to promote tumor growth and metastasis (5,(18)(19)(20)(21)(22)(23). The results of our previous study (24) indicated that the protein and mRNA expression of CXCR7 in Caco-2 cells was low compared with that in RKO, SW480, and HCT116 colon cancer cells. However, whether CXCR7 has similar functions in Caco-2 and HCT116 cells remains to be elucidated.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…CXCR7 is up-regulated in disease states including post-ischemic stroke [29,30], multiple sclerosis [31], Alzheimer's disease [32], epilepsy [33], rheumatoid arthritis [34], autism [35], and coronary artery disease [36]. Increased expression is also observed in many cancers, including prostate [16], pancreatic [37], ovarian [38], colon [39], kidney [40], liver [40], lung and breast [41] and CXCR7 is involved in the growth, metastasis and survival of these tumor cell lines. The receptor additionally functions as a coreceptor for various human immunodeficiency virus (HIV) strains [42].…”
Section: The Physiological Roles Of Cxcr7mentioning
confidence: 99%
“…CXCR7 has been implicated in the growth, metastasis, and survival of tumor cell lines such as prostate [16], glioma [12], bladder [50], pancreatic [37], Kaposi sarcoma [51], ovarian [38], cervical [52], colon [39], uterine [40], kidney [40], liver [40], stomach [40], lung and breast [41] as well as hepatocellular carcinoma [3]. CXCR7 is present on tumor endothelial, glioma and microglial cells, and is often colocalized with CXCL12 [12].…”
Section: The Role Of Cxcr7 In Cancersmentioning
confidence: 99%